Assessment of welfare status and income inequalities among cocoa farming households in Ondo State, Nigeria - Oguntade, A.E.; Adewumi, K.J.; Okafor, C.; Fatunmbi, T.E. (Cocoa Research Institute of Nigeria, 2015)
The main objective of this study is to assess the welfare status and the income inequalities among cocoa farming households in Ondo State, Nigeria. Primary data collected from sampled cocoa farmers were used for this study. Descriptive statistics were used to explain the socio-economic variables, farm specific characteristics, and indicators of household welfare status. Gini coefficient and index of dissimilarity were used to assess inequalities in the welfare status of the respondents. The result of the socio-economic analysis showed that most of the cocoa farmers were old, with an average age of 59.85 years. The mean other agricultural and nonagricultural incomes were N 34,694 and N 1,850 respectively. Also the majority of the respondents earned a total income ofN 300,000 or less with a mean of N 176,380 during the survey period. With regards to indicators of well-being, the number of rooms occupied by the respondents varied between two and sixteen with a mean of 5 rooms. All the respondents in the study area used iron sheets for their roofing material. Also most of the respondents lived in mud wall and mud brick houses while 30 percent lived in cement brick houses. About 51. 7 percent of the respon.dents I ived in houses that needed major repairs while 48.3 percent lived in houses that had sound structure. With regards to electricity, 60 percent of the respondents had no electricity supply in their houses. The majority, (95 percent) of the respondents used firewood. About 70 percent of the respondents did not use mosquito net on the windows .to protect their houses against mosquitoes and other flies. The assessment of the inequality in the welfare index yielded a Gini coefficient for welfare index of 0.2049, and an index of dissimilarity of 0.1161. This means that the cocoa farmers in the study area were not much better than one another in terms of we I fare status. The assessment of inequality in income distribution resulted in a Gini coefficient of 0.5249 and an index of dissimilarity of 0.3513, thus indicating that some inequality exists in the income distribution of cocoa farmers in the study area. The results indicate that there was more inequality in the distribution of the income than in the distribution of welfare index.